Seasonal apportionment of the sources of ambient air particulates in the city of Trieste. (19th March 2010) - Astel, Aleksander; Cozzutto, Sergio; Cozzi, Federico; Adami, Gianpiero; Barbieri, Pierluigi; Tsakovski, Stefan; Simeonov, Vasil
A PCA/APCS model was applied to PM2.5 data, which were collected for the Svevo and Muggia districts of the City of Trieste. The sampling campaigns covered the winter and summer periods of 2006. The set of investigated species comprised major inorganic ions, organic and elemental carbon and several Polyaromatic Hydrocarbons (PAHs) that were considered as probable or possible carcinogens by internationally recognised health and environmental agencies. Identified pollution sources included vehicle engine combustion ('traffic'), 'secondary emission', 'domestic combustion processes' and 'sea spray'. 'Secondary emission and combustion' dominated, with a total contribution over 74%. The traffic contribution was quantified as 2?16%, while sea spray was 4?13%. In general, possible or probable carcinogenic PAHs were related to the 'traffic' source. The high correlation coefficient (R² > 0.90) between the measured and predicted values proves that the PCA/APCS modelling is an efficient tool for the estimation of pollution sources' contribution to PM2.5 composition.